Studi Kasus Siswa Lamban Belajar di kelas IV Madrasah Ibtidaiyah (Diniyah: Jurnal Pendidikan Dasar, 2023)
This study aims to depict the experiences of slow learners in fourth grade and identify variables contributing to their difficulties. This qualitative research was conducted at MIN 2 Konawe Selatan, with seven slow-learning fourth-grade students and three fourth-grade teachers as informants. Data collection was carried out through observation, interviews, and documentation. The research data were then analyzed through stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that students experiencing learning difficulties are those who often delay completing homework, have cognitive abilities below standard, struggle to ask or answer questions during learning, and face challenges in reading and understanding the teacher's lessons. However, slow learners have the same good morals as normal children. The factors causing slow learning in students include low cognitive abilities, poor memory, concentration disorders during learning, difficulties in expressing ideas, poor academic achievement, language or communication problems, and emotional factors.Keywords: Slow Learners, student experiences, factors causing slow learning